2008
DOI: 10.1021/ja077865y
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Adsorption on MgO(100):  Energetics, Structure, and Role of Defects

Abstract: Abstract:The adsorption of Ca on the MgO(100) surface at 300 K has been studied using microcalorimetry, in combination with LEED, AES, ISS, work function, sticking probability measurements, and density functional theory (DFT) calculations. The MgO(100) thin films (∼4 nm thick) were grown epitaxially on a 1 µm thick Mo(100) single-crystal. The sticking probability of Ca on MgO(100) at 300 K is unity. On the basis of AES and ISS measurements, it was determined that Ca grows mainly as 3D particles on the MgO(100)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 86 publications
(159 reference statements)
9
70
1
Order By: Relevance
“…The calorimetry results in Table 4 are probably the best understood for the case of Ca on MgO(1 0 0), since this calorimetry study [77] included complementary DFT calculations by our collaborators (Graeme Henkelman and Lijun Xu) [77,81]. These DFT calculations showed that terrace sites bind Ca very weakly but that steps and kinks bind Ca very strongly.…”
Section: Metal Atom Adsorption On Oxide Surfaces and Metal Nanoparticmentioning
confidence: 92%
See 1 more Smart Citation
“…The calorimetry results in Table 4 are probably the best understood for the case of Ca on MgO(1 0 0), since this calorimetry study [77] included complementary DFT calculations by our collaborators (Graeme Henkelman and Lijun Xu) [77,81]. These DFT calculations showed that terrace sites bind Ca very weakly but that steps and kinks bind Ca very strongly.…”
Section: Metal Atom Adsorption On Oxide Surfaces and Metal Nanoparticmentioning
confidence: 92%
“…Here we will review in detail our studies of metal adsorption on ordered, 4-nm-thick MgO(1 0 0) thin films grown epitaxially on Mo(1 0 0) [24,68,70,71,[74][75][76][77][78]. These calorimetric measurements have allowed us for the first time to directly assess the energetic stability of metal atoms on a well-defined oxide surface and of metal atoms within metal nanoparticles supported on this oxide surface.…”
Section: Metal Atom Adsorption On Oxide Surfaces and Metal Nanoparticmentioning
confidence: 99%
“…Even on pristine NaCl͑100͒ surface, monatomic steps and kinks are also present inevitably. Indeed defects ͑vacancies, steps, etc.͒ are often decisive in chemical reactivity on insulator surfaces, [13][14][15] and they play an important role in both the adsorption geometry and the electronic structure. For example, a few experiments and theoretical studies suggest dissociative adsorption of water on NaCl͑100͒ in the presence of F s center.…”
Section: Introductionmentioning
confidence: 99%
“…37 19 If φ varies across the surface, large modulations in the image contrast occur due to the different contributions of the FERs to the electron transport. , 21 The fact that the oxide square pattern appears in the STM around the reported work-function values of the MgO/Mo system (3.3-3.9 eV) 25,38 This assumption is verified by measuring the bias position of FERs at different regions of the coincidence cell via dz/dV spectroscopy (Fig. 5b).…”
Section: (C) Electronic Properties Of Monolayer Mgo Filmsmentioning
confidence: 64%